Synthesis and characterization of post-sulfonated poly(arylene ether sulfone) membranes for potential applications in water desalination. (26th August 2019) - Choudhury, Shreya Roy; Lane, Ozma; Kazerooni, Dana; Narang, Gurtej S.; Jang, Eui Soung; Freeman, Benny D.; Lesko, John J.; Riffle, J.S.
Abstract: This study focuses on post-sulfonated polysulfone membranes for potential applications in desalination by reverse osmosis or electrodialysis. A series of controlled molecular weight (5000 and 10, 000 g/mol) polysulfones containing hydroquinone and their high molecular weight linear counterparts were synthesized using post-sulfonation of pre-formed polymers under mild conditions. The sulfonic acid groups were substituted on only the hydroquinone units. Amine terminated oligomers were crosslinked with a tetrafunctional epoxy molecule under suitable conditions to form membranes whereas the linear high molecular weight polymers were cast directly to form films with chain entanglements. Fixed charge concentrations of the membranes based on linear copolymers increased from 3.94 to 5.14 meq/mL when the ion exchange capacity was decreased from 1.30 to 0.88 meq/g. The fixed charge concentration of the networks cast from the 5000 g/mol oligomers increased from 4.04 to 6.23 meq/mL with a decrease in the ion exchange capacity from 1.51 to 0.90 meq/g. Graphical abstract: Image 1 Highlights: Polysulfone oligomers were synthesized and sulfonated after polymerization. Controlled MW oligomers with amine endgroups were crosslinked with epoxy reagents. The hydrated tensile properties of the membranes depend on water uptake.